2008
DOI: 10.1001/archpsyc.65.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Neural Plasticity in Patients With Schizophrenia

Abstract: It is possible that in schizophrenia, these deficits in neural plasticity are related to disturbances of gamma-aminobutyric acid, N-methyl-D-aspartate neurotransmission, or dopamine that may potentially account for the aberrant motor performance of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 41 publications
2
75
0
7
Order By: Relevance
“…Despite the consistent reduction of cortical plasticity in schizophrenia patients following different types of plasticity-inducing non-invasive brain stimulation (Hasan et al, 2013a;Daskalakis et al, 2008a;Frantseva et al, 2008;Oxley et al, 2004) and the association of smoking with functional and symptomatic improvements (D'Souza and Markou, 2012), the impact of nicotine intake via smoking on neuroplasticity in schizophrenia has not yet been investigated. To determine the physiological basis of the association between nicotine and neuroplasticity, we applied LTD-like plasticity-inducing cathodal tDCS to smoking and nonsmoking schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the consistent reduction of cortical plasticity in schizophrenia patients following different types of plasticity-inducing non-invasive brain stimulation (Hasan et al, 2013a;Daskalakis et al, 2008a;Frantseva et al, 2008;Oxley et al, 2004) and the association of smoking with functional and symptomatic improvements (D'Souza and Markou, 2012), the impact of nicotine intake via smoking on neuroplasticity in schizophrenia has not yet been investigated. To determine the physiological basis of the association between nicotine and neuroplasticity, we applied LTD-like plasticity-inducing cathodal tDCS to smoking and nonsmoking schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting changes in synaptic strength occur secondary to simultaneous activation of coactive cells (as theorized by Hebb 3 ), manifesting as LTP or LTD. There is strong neurophysiological evidence that plasticity is disrupted in schizophrenia, 1,8 a disorder that is commonly associated with deficits in learning and memory, in addition to delusions, hallucinations, and disorganization. 9 In the following sections, we outline the neural components of plasticity in the brain.…”
Section: Hebbmentioning
confidence: 99%
“…46 Deficits of neural plasticity involved with the main inhibitory neurotransmitter, GABA, have been documented in the brains of patients with schizophrenia. 1,47,48 Studies in memory processing (mediated in the amygdala and hippocampus) have shown abnormalities in schizophrenia, with altered PFC activation, decreased hippocampal volume, 49,50 and decreased GABAergic activity, particularly in hippocampal regions, demonstrated in postmortem studies. 51,52 These results have led to the hypothesis that there may not be adequate inhibition between the amygdala and hippocampus, especially in GABAergic interneurons in these regions, 51 resulting in disrupted LTP.…”
Section: Schizophrenia and Plasticitymentioning
confidence: 99%
“…Both GABA and NMDA receptormediated neurotransmission play an important role in use-dependent plasticity. 105 Daskalakis and colleagues 111 evalu ated use-dependent plasticity in 14 medicated and 6 unmedicated patients with schizophrenia and 12 healthy partici pants. A significant reduction of use-dependent plasticity was demonstrated in those with schizophrenia compared with healthy participants.…”
Section: Functional Consequences Of Disordered Inhibitionmentioning
confidence: 99%